Chile y su política exterior Trance y tránsito desde la Gran Guerra a la Guerra Fría (1914-1964) - Tapia Figueroa, Claudio; Rubilar Luengo, Mauricio (Ariadna Ediciones, 2023)
Chile and its foreign policy: Trance and transition from the Great War to the Cold War (1914-1964) is a collective book that brings together the advances and results of research related to the main problems that characterized Chile's international relations at the regional level. , continental and global from the vision that the Chilean political leaders and diplomats projected as part of a strategy of greater ties with the region and the world in a complex period of transition for Latin American countries. These States had to make decisions that impacted both politics and the economy, this being the main challenge that had to be faced during the time frame considered in the book, where the end of the belle époque, the development and consequences of the I World War, the emergence of the Union of Soviet Socialist Republics, the birth of the League of Nations, the consolidation of European totalitarianism and American hegemony in America, the crisis of 1929, the outbreak of World War II and its end , brought with it the transition to a critical stage for the world, such as the emergence of the Cold War with bipolarity, political and military conflicts, and the latency of nuclear destruction.